Techno economic analysis study of dry leaves via low temperature mechanism: article - Rosli, Muhamad Aiman Ashraf; Kasmuri, Nor Hazelah (2018)
Energy has played a crucial part in our daily life no matter what or where we live in this world. The common source of energy is fossil fuels. This fossil fuels are digged and sourced from undersea and brought to the surface. However, this source is unreliable as it causes pollution, unrenewable, and depleting over the years. That is why, a better and more reliable source of energy which is biomass is proposed in this paper. That is because biomass can be obtained from anywhere and anytime. It provides the same amount of energy and have the same purpose of fuels if treated and processed correctly. Biomass used as a fuel is renewable and always available. The carbon dioxide that are released by the biomass fuel is taken back by plants. This way, the fuel would not cause any pollution to the environment and at the same time it produced oxygen. There are several ways of converting biomass into source of energy which in this study, the torrefaction and pyrolysis process will be used as a guideline process. Both processes have the same purpose which is converting the biomass into 3 products which are biochar, biofuels and syngas. However, the equipment and yield will differ accordingly. The biomass that will be use as raw materials is dry leaves. The ultimate analysis of the dry leaves will be obtained first and around 10,000 kg of dry leaves are used as a basis at the starting process. A simulation will be created to compare the two process in terms of yield and cost. The tools used for this study is Aspen Hysys. For pyrolysis, a yield of coal, fuel, and gas obtained are 23.4%, 48.8% and 27.8% respectively while torrefaction obtained a yield of 70.36%, 11.51% and 18.13% respectively.